La música, aporte innovador para la educación básica (2019)
The present paper is focused on some activities developed by the musical program of the “Licenciatura en Educación Básica” which belongs to the Faculty of Distance Learning at Universidad Pedagógica y Tecnológica de Colombia regarding the methodology, cross curricular subjects and outreach activities. This program offers students the possibility to study musical education in which knowledge and musical aspects are proposed for future teachers with the aim to strength their competences and skills needed in the classroom. The program also suggests a research project inside the curriculum that includes previous background related other disciplines of knowledge, supporting the solution of struggles that rise in the classroom. Likewise, the students who make part of the Faculty may belong to different musical groups that later on are projected to the community itself.